Human Factor in State Government Reforms - Marčinskas, Albinas (Ekonomika, 1998)
Government reforms in Lithuania from chaotic stile are developing into the clearer strategy, oriented into European public administration cultural space. Reforms, impeded by historically formed bureaucracy traditions, could be įveiktos by wider using of human factor. In all levels (state, districts, municipalities) it would be acceptable sociological referendums, psychological training of public officers? valdininkų for reforms and their participating in reforms. Exceptionally meaning for cardinal public administration quality changes would have the practice of monitoring. The special place in it would be for government public administration services for consumer services.